Authority of the Commercial Court in Settling Trademark Rights Disputes - Koto, Ismail; Nainggolan, Ibrahim; Rahimah, Rahimah (Jurnal Hukum Replik, 2025)
Trademark rights are regulated in Law No. 20 of 2016 concerning Trademarks and Geographical Indications. According to Law No. 20 of 2016 concerning Trademarks and Geographical Indications, to obtain rights to a trademark, the trademark must be registered with the Directorate of Trademarks of the Ministry of Law and Human Rights of the Republic of Indonesia according to the constitutive system, in other words, to obtain legal protection for trademark rights, the trademark must be registered by its owner with the Trademark Directorate and after being officially registered in the name of the owner, a trademark certificate will be issued. Law No. 20 of 2016 concerning Trademarks and Geographical Indications, specifically in Article 21 paragraph (1) letters b and c, Article 83 paragraph (2), and reinforced by the Explanation of Article 21 paragraph (1) letter b, Explanation of Article 76 paragraph (2), and Explanation of Article 83 paragraph (2). Indonesia adopts a Trademark registration system with a constitutive system. This system requires trademark registration so that a trademark can receive protection, this system is also known as the first to file system. The applicable procedural law in the process of filing a dispute in the field of intellectual property rights is the Civil Procedural Law as with the civil procedural law in civil cases handled by the District Court in the general judicial body environment. The process of filing a lawsuit for an intellectual property rights dispute has been regulated through laws and regulations in Indonesia, in accordance with the provisions of the applicable law on each intellectual property right, where the lawsuit is processed through the Commercial Court